The role of brand ambassadors in customer excitement-A survey study of the opinions of some customers of Asia Cell Communications Company in Misan Governorate - Lecturer: Hind Naeem Hoshi (Peerian Journals Publishing, 2025)
The aim of this current research is to know what is the role of brand ambassadors in exciting the customer, by relying on a modern marketing method represented by relying on famous personalities in promoting the services of Asia Cell Company located in Misan, based on two variables: the independent variable (brand ambassadors) with its dimensions (vision, credibility, attractiveness, strength) and the dependent variable (customer excitement) one-dimensional, where a sample of (300) customers was taken for the sample studied and the research reached a set of conclusions including (There is a relationship of influence of the brand ambassadors variable in customer excitement, and we conclude from this relationship: If you want Asia Cell Company Excite their customers, get more customers, expand their market share and increase their profits. Brand ambassadors can achieve this goal.) The recommendations include (Asia Cell Company’s focus on caring for brand ambassadors by dividing them into their effective role in achieving marketing excitement among customers, and paying attention to conducting a periodic review to know the opinion of its customers about all the services it provides that satisfy them and motivate them to purchase them).
Keywords: Brand Ambassadors-Excitement customer; Asia Cell